Evaluation of the level of vascular expansion in terms of the test of the Oxyade between the athletes' pioneers and their staff members - Hazem, Abeer; Muhammed, Jumaa (Journal of Physical Education, 2019)
The compound Nitric Oxide of newly discovered compounds and uses the test of nitric oxide in the medical field to measure the rate of expansion of blood vessels, and therefore it is also necessary in the field of sports to give specialists of academics and trainers of the rate of expansion of blood vessels in athletes and non-athletes and from here the researcher took this test And put it into use in the field of sports as well as non-athletes to determine the rate of expansion of blood vessels they have based on the famous saying (prevention is better than cure), and health problems is that many people do not realize the importance of sport than their own family members injured interpreted many diseases with age  Therefore, the aim of the research was to use the nitric oxide test on 60 individuals divided into four groups of 15 groups in terms of age and weight. The first group are athletes who are still practicing sports at the age of 50-6 years. The second group is the students of the school of excellence (age 15-16) who do not exercise and the fourth group of players aged (15-16) years. The researcher assumes that there are There are statistically significant differences in the test between the two leading athletes and their peers Office staff and between the players and students of the School of Excellence  using the nitric oxide test for expansion Blood vessels for athletes and non-athletes as well as recommends the need to continue to exercise regularly and to maintain the health of the individual and to prevent diseases.